Enhancing Vocabulary, Autonomy, and Engagement in L2 Regimented Learning Environments: The effectiveness of digital tools within flipped learning approaches - ALHUSSAN‬‏, ‪ABDULAZIZ (2024)
This thesis investigates the feasibility of utilising technology to enhance English instruction within a regimented military Academy. The significance of this study lies in its novel educational setting which provides a unique opportunity to explore the effects of English exposure in an environment free from external influences like mobile phones and internet access. This approach helps to address potential confounding factors present in earlier studies. Specifically, this thesis explores the impact of using a digital tool called Transparent Language Online (TLO) on promoting cadets’ vocabulary learning, autonomy and engagement. Through conducting two distinct empirical studies, the research aims first to establish a comprehensive understanding of the study context and explore the opportunities and challenges associated with prior digital learning experiences at the Academy (Chapter 4). The findings and implications of this study serve as a foundation for designing the subsequent experimental study (Chapter 5), which involved two groups: a digital-flipped group (n=22) and a paper-based flipped group (n=21). Both groups followed identical lesson plans and learning procedures, differing only in their use of the TLO for pre-class revision and in-class learning, versus bilingual vocabulary lists and worksheets for the paper-based group. The findings reveal that while the digital tool did not significantly affect students’ vocabulary acquisition, it proved effective in improving retention, as evidenced by a four-week delayed test. This underscores the tool's potential in promoting vocabulary retention over acquisition due to its integrated features, such as spaced-interval repetition and multimodalities. Furthermore, integrating the tool within a flipped approach notably fosters cadets' autonomy and reduces the reliance on the instructor. However, excessive cadets’ reliance on the digital tool during lessons reduces teacher-student interaction. Similarly, both groups perceive formative assessments, irrespective of format (digital or paper-based), as effective in promoting consistent learning, enhancing achievement, and alleviating final exam-related stress. Nevertheless, the digital tool significantly enhances the learning environment and contributes to improving cadets' focus and concentration on learning tasks throughout the lessons. Moreover, the utilisation of the digital tool demonstrates a significant impact on encouraging cadets to dedicate additional time and effort to reviewe pre-class materials, resulting in enhanced class performance. This thesis makes a significant contribution to the literature on flipped learning methodology in EFL contexts by exemplifying how a blended learning framework can be customised to align with learners' needs within the available infrastructure. In addition to its contribution to flipped learning methodology in EFL contexts, the thesis also sheds light on learning processes within a controlled environment where incidental learning outside the classroom is limited, enriching our understanding of learner engagement and autonomy within such settings. Moreover, this work offers valuable insights for decision-makers within military academies, elucidating key factors conducive to integrating technology into language learning curricula. Therefore, it is imperative that policymakers prioritise thorough planning and analysis of learners' requirements to establish effective blended learning environments.